Survei Demam Secara Massal Berhasil Mengendalikan Wabah Malaria Di Pulau Bungin Kabupaten Sumbawa Nusa Tenggara Barat : Pelajaran Tentang Pentingnya Deteksi Agresif Di Salah Satu Pulau Terpenting Di Dunia: The Mass Fever Survey Was A Success In Controling Outbreak Malaria In Bungin Island, Sumbawa District, West Nusa Tenggara : Lesson In The Importance Of Aggressive Detection On One Of The Most Populous Islands In The Worlds - Philip Habib; Ahmad Taufik S; Adnanto Wiweko; Didit Yudhanto; Mohammad Rizki; Lalu Hamri Fikri; Mulyanto Mulyanto (LPPM Universitas Mataram, 2023)
Bungin Island is a very small island where population density is high, with a total population of 3,287 in a 2 kilometer-square area. The Annual Parasite Index (API) on Bungin Island in 2006 was 16,0 per thousand people. Outbreaks of malaria in Bungin Island are correlated with several controllable factors. The goal of this study is to aggressively detect and treat malaria, as well as to identify the factors that contribute to malaria outbreaks. Data was collected from the resident of Bungin Island who came to Sub-Primary Health Center Bungin Island in October 1, 2007. The data collection when outbreak malaria occurs, consisted of anamnesis, physical examination and test for type of malaria. A finger prick blood sample was collected and tested with rapid diagnostic test (RDT) for type of plasmodium. Treatment base on standard treatment for malaria from Indonesian Health Department was given to the subjects were malaria positive. The total 201 subjects was tested by RDT, in which 93 positive malaria (46,27%). Most of them were infected by Plasmodium vivax (97.85%) and only 2 subjects were infected by Plasmodium falciparum (2.15%). There were 23 subjects (24.27%) showed malaria positive without clinical symptoms. The subjects positive malaria with clinical symptoms, 8.57% were found to have spleenomegaly and 7.14% were found to have hepatomegaly. Incidence of malaria decrease siginifantly in few week after aggresive detection and appropriate treatment. A few years later, malaria incidence was disappeared. The incidence of malaria in Bungin Island was high when an outbreak occured. Aggressive detection with mass blood survey could find asymptomatic malaria in the population and appropriate treatment would decrease positive malaria until it disappeared.